Mapeamento de áreas inundáveis na região do Baixo Jaguaribe (Ceará) utilizando imagens Sentinel-1 e Sentinel-2 - Silva Neto, Tomaz Alexandre da (2023)
Floodplains are extremely important for maintaining life on land, as they are directly related to hydrological dynamics. Because they are flat areas, with low slopes and close to watercourses, they become preferred areas for irrigation projects, agricultural cultivation, grazing and the construction of roads. These activities generate negative impacts such as deforestation, silting up of rivers, disorderly occupation, flooding, water contamination, etc. Synthetic Aperture RADAR (SAR) data has shown excellent results in mapping and monitoring these areas due to its high revisit frequency, spatial resolution and the fact that it is not influenced by the atmosphere. The aim of this study was to map the flood areas in a region of the Lower Jaguaribe River located near the municipality of Russas, in the state of Ceará, for two different climatic seasons for the year 2021, using SAR images. The SAR Backscatter Threshold technique was used on Sentinel-1 satellite images. These images were pre-processed and a multi-temporal cube was built using the Google Earth Engine platform to observe the behaviour of the targets over time. As a result, the flooded areas were delineated by comparing the flooded and dry periods. The flood peak occurred in July, corresponding to an area of 121.18 ha and the dry period occurred in November, covering an area of 32.38 ha. The main types of Land Cover and Land Use of the flooded areas and Permanent Protection Areas (PPAs) were identified. It was found that in the flooded areas, more than 50% of the area corresponds to the exposed soil class. Around 3% of the area corresponds to human occupation. As for the use and occupation of restricted areas, it was identified that around 20% of these regions are made up of the classes Non-agricultural anthropogenic area and Agricultural anthropogenic area, generating a conflict in relation to the use of these areas in accordance with Federal Law No. 12,651/12 (Forest Code). This information serves as a basis for the type of management that should be adopted by the responsible bodies. By accurately identifying areas prone to flooding, it is possible to take preventative and mitigation measures, such as building flood control infrastructure, as well as contributing to the development of public policies aimed at identifying priority areas for the implementation of soil conservation practices and the recovery of degraded areas